The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/cctc.202000488
|View full text |Cite
|
Sign up to set email alerts
|

A Visible‐Light Promoted Amine Oxidation Catalyzed by a Cp*Ir Complex

Abstract: Through a rapid screening of Cp*Ir complexes based on a turnon type fluorescence readout, a [Cp*Ir(dipyrido[3,2-a : 2',3'-c] phenazine)Cl] + complex was found to catalyze the blue-light promoted dehydrogenation of N-heterocycles under physiological conditions. In the dehydrogenation of tetrahydroisoquinolines, the catalyst preferentially yielded the monodehydrogenated product, accompanying H 2 O 2 generation. We surmise that this mechanism may be reminiscent of flavin-dependent oxidases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Previously, our group reported that the photocatalytic dehydrogenation of N-heterocycles proceeds on the dppz ligand of [Cp*Ir(Cl)dppz] + . 32 More recently, photocatalytic NADH oxidation by 1 has been reported. 33 In both cases, the dppz ligand has been proposed to act as an electron acceptor to form reduced dppz (dppzH 2 ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, our group reported that the photocatalytic dehydrogenation of N-heterocycles proceeds on the dppz ligand of [Cp*Ir(Cl)dppz] + . 32 More recently, photocatalytic NADH oxidation by 1 has been reported. 33 In both cases, the dppz ligand has been proposed to act as an electron acceptor to form reduced dppz (dppzH 2 ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition to these interesting features of the dppz ligand, it has also been reported to act as a redox center in photocatalysis. Previously, our group reported that the photocatalytic dehydrogenation of N -heterocycles proceeds on the dppz ligand of [Cp*Ir­(Cl)­dppz] + . More recently, photocatalytic NADH oxidation by 1 has been reported .…”
Section: Resultsmentioning
confidence: 99%
“…Given the sustained interest in photocatalysis over the last decade, [16][17][18][19] a growing number of examples for greener metal-free photocatalytic transformation of amines to imines were revealed to promote this transformation as a synthetically robust reaction manifold. [20][21][22][23][24][25] In this context, we came across an amine that was spontaneously converted to the corresponding imine under ambient conditions with dioxygen (Fig. 1C).…”
Section: Current Topicsmentioning
confidence: 99%
“…In this sense, artificial metalloenzymes based on the insertion of organometallic complexes on the protein structure has been recently synthesized. [13][14][15][16][17][18][19] However, this required a timeconsuming in the preparation of the organometallic compound or required different modification of the protein for site-selective insertion of the metal. Another issue in this aspect is that mainly this artificial enzyme is water soluble as natural enzyme, presenting similar problems of compatibility in some experimental conditions or being required additional steps.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alternative strategies, where both systems conserved full activity, are necessary. In this sense, artificial metalloenzymes based on the insertion of organometallic complexes on the protein structure has been recently synthesized [13–19] . However, this required a time‐consuming in the preparation of the organometallic compound or required different modification of the protein for site‐selective insertion of the metal.…”
Section: Introductionmentioning
confidence: 99%